Antibiotic Metabolites from a Marine Pseudomonad - Wratten, Stephen J. (Antimicrob Agents Chemother, 1977)
An antibiotic-producing pseudomonad was isolated from a seawater sample from a La Jolla, Calif., tidepool. The pseudomonad produces two novel antibacterial compounds, 2-n-pentyl-4-quinolinol and 2-n-heptyl-4-quinolinol. It also synthesizes indole-3-carboxaldehyde, 6-bromoindole-3-carboxaldehyde, and the known antibiotic p-hydroxybenzaldehyde. Each of these compounds was identified by analysis of spectral data, and the structures were confirmed by synthesis or comparison with authentic samples.